Pendampingan Pembelajaran Daring Parsial dan Terpadu Berbasis 3CM (Cool-Critical-Creative-Meaningful) Learning untuk Mengatasi Kejenuhan Belajar dan Kreativitas Implikasi Dampak Covid-19 - Wahyudi Wahyudi; Tri Nova H. Yunianta; Erlina Prihatnani; Kristina Roseven Nababan; Dani Kusuma; Anisa Rizki Amalia; Bella Ayu Permatasari; Cindy Aprillya Sidarta; Bagas Prima Kristanto; Syera Trivena Dessiane; Erlin Prasetyo (Universitas Kristen Satya Wacana Salatiga, 2021)
The Covid-19 pandemic has a huge impact on aspects of human life, one of which is in the world of education. Schools, teachers, learners and parents were also affected. The learning process that should be able to be performed in school with the assistance of teachers directly, now must move home by online with parental assistance. Accordance with the policy of the Ministry of Education and Culture of the Republic of Indonesia, namely Learning From Home by online. This sudden change in the way of learning makes it difficult for teachers to prepare and carry out learning. Ordinary learning is still difficult to do moreover learning that demands the creativity of teachers and learners. The ability of teachers to utilize technology is not good enough, so it becomes difficult if they have to do online learning. From the results of the survey, almost all learning activities are performed by sending materials and assignments, then tasks are done by students and the results are sent through WhatsApp groups (89.7% of 271 respondents). Learners become saturated and want to return to study in school (72.12%) which has an impact on decreasing opportunities to do creative activities for learners. The solution of this problem is to provide online learning facilities and support for teachers in preparing learning as well as for students and parents during the learning process. This will help teachers in preparing online learning so that teachers have enough time to develop materials and media that can be uploaded in online classes. In addition, there will be standards for organizing online classes so as to give students the opportunity to learn well, fun and can return creatively. One of the online learning designs that teachers can use is the design of online learning based on 3CM (Cool-Critical-Creative-Meaningful) learning. This learning provides students with the opportunity to develop critical, creative, meaningful thinking skills in fun and challenging ways in both partial and integrated online. The product of this activity is: 1) partial and integrated online classes; 2) Scientific articles that can be published in Community service journals.